2020
DOI: 10.1039/d0sc03240a
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine-5 methylation-directed construction of a Au nanoparticle-based nanosensor for simultaneous detection of multiple DNA methyltransferases at the single-molecule level

Abstract: DNA methylation at cytosine/guanine dinucleotide islands (CpGIs) is the most prominent epigenetic modification in porokaryotic and eukaryotic genomes. DNA methyltransferases (MTases) are responsible for genomic methylation, and their aberrant activities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Single-molecule detection has gained overwhelming attention due to high signal-to-noise ratio, low sample consumption, and ultrahigh sensitivity. [41][42][43][44][45][46] We used two lung cancer biomarkers miR-155 and miR-21 as the targets. The presence of miR-155 and miR-21 can initiate three consecutive amplification reactions (i.e., cyclic strand displacement amplification (SDA), APE1-assisted cyclic cleavage, and rolling circle amplification (RCA)), converting extremely low abundant target miRNAs to abundant Cy5/Cy3 fluorophores-encoded DNA products whose digestion releases larger numbers of fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule detection has gained overwhelming attention due to high signal-to-noise ratio, low sample consumption, and ultrahigh sensitivity. [41][42][43][44][45][46] We used two lung cancer biomarkers miR-155 and miR-21 as the targets. The presence of miR-155 and miR-21 can initiate three consecutive amplification reactions (i.e., cyclic strand displacement amplification (SDA), APE1-assisted cyclic cleavage, and rolling circle amplification (RCA)), converting extremely low abundant target miRNAs to abundant Cy5/Cy3 fluorophores-encoded DNA products whose digestion releases larger numbers of fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…18 nanoparticles (AuNPs) and silver nanoparticles (AgNPs) are usually used to construct scattering probes to analyze and detect biomolecules, drugs, and food. 22,23 Since dark-field microscopy (DFM) has the advantages of high signal-to-noise ratio and sensitive response, it is often used to obtain the resonance light scattering signal of plasmonic nanoparticles. 24−26 At present, DFM is widely used in real-time and effective analysis of chemical reactions at the level of single nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plasmonic nanoparticles have bright and stable light scattering signals due to their localized surface plasmon resonance (LSPR) optical characteristics. The LSPR of plasmonic nanoparticles has properties that are adjustable and related to different materials, morphologies, and sizes. Due to these advantages, noble metals such as gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) are usually used to construct scattering probes to analyze and detect biomolecules, drugs, and food. , Since dark-field microscopy (DFM) has the advantages of high signal-to-noise ratio and sensitive response, it is often used to obtain the resonance light scattering signal of plasmonic nanoparticles. At present, DFM is widely used in real-time and effective analysis of chemical reactions at the level of single nanoparticles. …”
Section: Introductionmentioning
confidence: 99%
“…et al constructed a gold nanoparticle-based nanosensor that can detect multiple DNA MTase enzymes at the single molecule level; simultaneously, Wang, Z.-Y. et al have recently reported a chemiluminescent sensor for bacteria and human DNA MTase quantification. , Although great progress has been made in the development of methods for monitoring the real-time activity of DNA MTases, the requirement for restriction endonucleases in these assays limits their application in compound screening, as the restriction endonuclease may be sensitive to antitumor drugs. , …”
Section: Introductionmentioning
confidence: 99%